1952: a poesia de O Estranho de Max Martins - ALENCAR, Melissa da Costa (Universidade Federal do Pará, 2012)
This dissertation studies the poetry of the book O Estranho, 1952, the poet from Para Max Martin and his knot with modern poetry. For this, we consider the poetry of Max dialogues with the texts of Brazilian poets of national renown and universal. According to Haroldo de Campos, a poetic relationship with the literary tradition and the project that requires the artistic text is a meeting between codes, in a rare ability to transfer the ephemeris even closer to the horizon of doing in the creation, fighting hand to hand with the word. This struggle with the verb is a fundamental part in the game poetic Max Martins. O Estranho, by questioning the place of poetry in his own time, the poet breaksdown the text and reveals the man and writing in the margins. The poetry of the stranger – the gauche drummondiano term suggests – is a “dialect” perhaps uninteligible to some. As the poem suggests that initial work, the language can even be incomprehensible, hence the word “stranger” (the title of the book and the first poem), in other words, a language shock, which is strange with reality, however, is whatever the poet, the transmutation of everyday reality in poetry. In this paper, we draw the relevant aspects of modern lyricism from a study on the concepts of Modern, Modernity and Modernism, passing quickly through modernism in Brazil, for to get to Pará modernism, and specifically the generation of Max. Finally, we propose an interpretation of the poems from the book (especially analyzing them in light of critical and reflective reading Benedito Nunes, the first critic of poems by Max Martins). Was also made publishing history of the poems before and after the publication of O Estranho. With this, we intend to contribute to literary studies regarding talk more al lenght about the important aspects of the poetry of Max Martins, especially about his initiation into the poetic world.